2015
DOI: 10.1111/1440-1681.12484
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ADP‐ribose)polymerase 1 inhibition protects against age‐dependent endothelial dysfunction

Abstract: Age-related endothelial dysfunction is closely associated with the local production of reactive oxygen species (ROS) within and in the vicinity of the vascular endothelium. Oxidant-induced DNA damage can activate the nuclear enzyme poly(ADP-ribose) polymerase 1 (PARP-1), leading to endothelial dysfunction in various pathophysiological conditions. The present study aimed to investigate the role of PARP-1 in age-dependent changes in endothelial cell function and its underlying mechanism. Wild-type (WT) and PARP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 30 publications
(49 reference statements)
1
4
0
Order By: Relevance
“… 16 In the present study, we showed that axitinib decreases NO signaling in human endothelial cells, effects that are reversed by olaparib. This is further corroborated by others showing that PARP inhibition improves hyperhomocysteinemia‐ 30 and age‐dependent endothelial dysfunction 31 by regulating NO bioavailability. PARP‐1 inhibition was also shown to improve endothelial function by enhancing VEGFR2/Akt/BAD phosphorylation, and by reducing inflammation via NF‐κB.…”
Section: Discussionsupporting
confidence: 77%
“… 16 In the present study, we showed that axitinib decreases NO signaling in human endothelial cells, effects that are reversed by olaparib. This is further corroborated by others showing that PARP inhibition improves hyperhomocysteinemia‐ 30 and age‐dependent endothelial dysfunction 31 by regulating NO bioavailability. PARP‐1 inhibition was also shown to improve endothelial function by enhancing VEGFR2/Akt/BAD phosphorylation, and by reducing inflammation via NF‐κB.…”
Section: Discussionsupporting
confidence: 77%
“…Many other cellular processes also rely on PARP-1 signaling, and abnormal PARP-1 activity has been attributed to various age-related diseases, including hypertension [2325]. Consistent with these findings, inhibiting PARP-1 activity in endothelial cells protects against endothelial dysfunction [26, 27] and PARP-1 inhibitors are under consideration as a treatment for pulmonary hypertension [28]. However, differential expression of PARP-1 has not been investigated with respect to health disparities in essential hypertension.…”
Section: Introductionmentioning
confidence: 88%
“…For instance, in aging rats, treatment with the PARP inhibitor INO-1001 reduces cardiovascular disorders [ 126 ], and treatment with the PARP inhibitor PJ34 improves myocardial contractile function and restores endothelial function [ 127 ]. Furthermore, PARP-1 inhibition may protect against age-dependent endothelial dysfunction, potentially by regulating NO bioavailability via iNOS [ 128 ].…”
Section: The Nucleus-mitochondria Connection and The Importance Ofmentioning
confidence: 99%